Chemical composition and antimicrobial activity of Myrtus communis essential oils from Algeria - YACINE MOHAMADI; TAKIA LOGRADA; Messaoud Ramdani; GILLES FIGUEREDO; PIERRE CHALARD (Society for Indonesian Biodiversity, 2021)
Abstract. Mohamadi Y, Lograda T, Ramdani M, Figueredo G, Chalard P. 2021. Chemical composition and antimicrobial activity of Myrtus communis essential oils from Algeria. Biodiversitas 22: 933-946.  The objectives of this study were to determine the chemical composition and the antibacterial activities of Myrtus communis essential oils. The aerial parts of the myrtle were collected from nineteen localities of the Algerian coast, and subjected to hydrodistillation. The chemical composition of essential oils was analyzed using gas chromatography coupled with mass spectrometry (GC/MS). The antibacterial activity was evaluated by the disk diffusion method against ten bacterial species. Essential oils of M. communis was pale yellow oils, very fragrant, with an average yield of 0.68 ± 0.6%. Forty-six compounds were identified, representing an average of 99.17 ± 0.6% of total oils. The ?-pinene was the most abundant component in the essential oils of all populations studied, with a mean of 50.1 ± 10.3%, followed by 1,8-cineole (22.27 ± 4.32%), limonene (5.16 ± 2.67%), linalool (3.79 ± 2.97%), ?-terpineol (2.75 ± 1.12%), geranyl acetate (1.95 ± 0.7%) and methyl eugenol (1.40 ± 0.98%). Myrtenyl acetate was only observed in four populations with significant levels (from 10.66 to 20.94%). Six chemotypes have been identified in these oils. The ?-pinene – 1,8-cineole - limonene chemotype was found in the majority of populations. The chemotype of ?-pinene - 1,8-cineole - ?-terphenyl acetate characterizes the Oued El-Aneb population. The ?-pinene - neryl formate - limonene chemotype is observed in the Honaïn population. The remaining populations are characterized by myrtenyl acetate. The essential oils of M. communis were effective against Staphylococcus aureus ATCC 25923, Salmonella enterica ATCC35659, Proteus mirabilis, and Escherichia coli ATCC 25922; however, no significant effect was observed on Klebsiella pneumonia ATCC 700603 and Serratia liquefaciens.